Improvement of Protein Bioavailability by Solid-State Fermentation of Babassu Mesocarp Flour and Cassava Leaves - Morales, E. M. [UNESP]; Domingos, R. N.; Angelis, D. F. [UNESP] (Springer Nature, 2018)
Purpose: The worldwide demand of food is continuously increasing along with its selling price. Higher food costs affect the access of poor communities to nutritious food, so become a priority problem to be solved, according to the United Nations. This study provides an alternative and viable contribution to the enrichment of food for poor communities using agricultural byproducts. Methods: Samples of a mixture of cassava leaves and babassu mesocarp fermented in solid-state way with Rhizopus oligosporus were submitted to evaluation of protein quantity and quality, by the comparison of the digestibility before and after the solid-state fermentation. The assessment of essential amino acids, relative nutritional value and protein digestibility-corrected amino acid score (PDCAAS) estimated the quality of the protein. Results: The solid-state fermentation increased by 15.2% the amount of crude protein and improved quality, resulting in a food with relative nutritional value for 98.18%, equating to the casein (100%). The PDCAAS of fermented mixture (BMF + 32% CLF) showed results similar to beans and protein textured soybean (PTS) reported, indicating a good source of amino acids (0.6037 to the fermented mixture, 0.6296 for beans and 0.6481 to PTS). The SSF also reduced by 94.18% the amount of cyanide present in the mixture, which is a substance derived from the cassava leaves. Conclusion: By the obtained results, it was observed that the use of SSF in byproducts from agroindustry can produce more nutritious food for humans by the transformation of energetic food in structural food which has a higher amount of proteins.
Keywords: Amino acid; Babassu mesocarp; Cassava leaves; PDCAAS; Relative nutritional value; Rhizopus oligosporus